The effect of oil palm trunk fiber on characterization of natural rubber - Mohamad Azlan Syah, Dzulkafli (2010)
The strength of a material to stress depends on the chemical bonds found in the chemical structure of the material itself. This thesis deals with the effect of different filler loading on the natural rubber vulcanizates so that the dynamic mechanical properties of vulcanized natural rubber can be obtained. The objective of this thesis is to study the effect of different filler loading or amount of filler loaded on natural rubber that is Standard Malaysian Rubber 10 (SMR-10). For this study, natural filler that is oil palm trunk fiber which is varies from 0 to 50 phr have been used as an additive to strengthen the chemical bonds of natural rubber as well as other chemicals that were added to natural rubber. Rubber compounds filled with natural fillers and other chemical additives is prepared using a two roll mill and the characteristics of the mechanical properties are studied and analyzed to determine the effect on the strength of natural rubber when natural filler is added as filler. In this thesis, there is description on background of the natural rubber and the characteristics of cured natural rubber after being treated by fillers. Most commonly used fillers by industry for curing natural rubber is carbon black and calcium carbonate which is can be categorized by black filler and non-black filler. But for this study, these materials will be used as a reference and oil palm trunk fiber is used as replacement and the effects of natural fillers are studied and analyzed. The functions for each material that is stated above might be vary based on their physical and chemical properties data but all fillers generally increase the tensile strength and modulus of vulcanized natural rubber into particular level.